Effects of interaction between ectomycorrhizal fungal and mycorrhiza helper bacteria on Picea abies seedlings growth - Sheno Amini; Moazzam Hassanpour Asil; Jamalali Olfati; Sedigheh Mousanejad (Caspian Journal of Environmental Sciences, 2023)
Early growth and establishment success of Picea abies is poor, so ectomycorrhizal (ECM) fungi can be used to promote survival, establishment, as well as the growth of seedlings. This study aimed to evaluate the effect of valuable ECM fungi symbiosis and mycorrhiza helper bacteria (Bacillus cereus) on the growth of P. abies. The treatments included B. cereus, ECM fungi of Cantharellus cibarius, Amanita caesarea, Boletus edulis, three combined treatments (Bacillus + ECM fungi), and control. 2-month-old seedlings were inoculated with fungi and bacteria. Then root mycorrhization percent, morphological traits, chlorophyll content and nutrient uptake were evaluated in 15 months after plant inoculation. The results indicated that mycorrhization was significantly influenced by applied treatments. The highest (50.33%) and lowest (27.67%) mycorrhizations were obtained by B. edulis + B. cereus and C. cibarius, respectively. The combination treatments dramatically increased the plant height, stem and root dry weight, total chlorophyll, absorption of potassium and nitrogen compared to the control. The combined inoculation with B. cereus + B. edulis also resulted in an increase in K and Ca uptake as well as chlorophyll a compared to control. The lowest values for all evaluated traits except Ca uptake were obtained by control. Moreover, the highest values for all traits were observed in plants co-inoculated with B. cereus + B. edulis. In conclusion, the results suggested that the ECM fungi, especially Boletus, had a symbiosis with Norway spruce. The symbiosis was also improved by B. cereus.